Patient-reported impact of myasthenia gravis in the real world: protocol for a digital observational study (MyRealWorld MG). Issue 7 (20th July 2021) - Berrih-Aknin, Sonia; Claeys, Kristl G; Law, Nancy; Mantegazza, Renato; Murai, Hiroyuki; Saccà, Francesco; Dewilde, Sarah; Janssen, Mathieu F; Bagshaw, Emma; Kousoulakou, Hara; Larkin, Mark; Beauchamp, Jon; et al.
Abstract : Introduction: Myasthenia gravis (MG) is a rare, chronic, autoimmune disease, mediated by immunoglobulin G antibodies, which causes debilitating muscle weakness. As with most rare diseases, there is little patient-reported data with which to understand and address patient needs. This study explores the impact of MG in the real world from the patient perspective. Methods and analysis: This is a 2-year prospective, observational, digital, longitudinal study of adults with MG, resident in the following countries: the USA, Japan, Germany, France, the UK, Italy, Spain, Canada and Belgium. The planned sample size is 2000. Recruitment will be community based, via patient advocacy groups, social media and word of mouth. Participants will use a smartphone application (app) to check eligibility, provide consent and contribute data. Planned data entry is as follows: (1) personal profile on enrollment—covering demographics, MG characteristics and previous care; (2) monthly event tracker—current treatments, healthcare visits, treatment-related adverse events, productivity losses; (3) monthly selection of validated generic and disease-specific patient-reported outcomes instruments: EQ-5D-5L, Myasthenia Gravis Activities of Daily Living, Myasthenia Gravis Quality of Life 15-item revised scale, Hospital Anxiety and Depression Scale and Health Utilities Index III. Analyses are planned for when the study has been running in most countries for approximately 6, 12, 18 and 24 months. Ethics and dissemination: The study protocol has been reviewed and granted ethics approval by Salus IRB for participants resident in the following countries: Germany, the UK and the US. Local ethics approval is being sought for the following study countries: Belgium, Canada, France, Italy, Japan and Spain. Study results will be communicated to the public and participants via conference presentations and journal publications, as well as regular email, social media and in-application communication. Trial registration number: NCT04176211 .